Self-assembly of amphiphilic polyphenylene dendrimers with different surface functionalization in solvent/non-solvent mixtures - Weigold, Svenja; Brödner, Kerstin; John, Torsten; Freudenberg, Jan; Bunz, Uwe H. F.; Weil, Tanja; Fytas, George; Müllen, Klaus (Macromolecular chemistry and physics, 2025)
This work compares the self-assembly of nanometer-sized amphiphilic Janus-type and patched polyphenylene dendrimers (PPDs) in solvent/non-solvent mixtures utilizing static and dynamic light-scattering measurements. First- and second-generation (G1 and G2) dendrimers are functionalized with substituents of different polarity, i.e., polar neo-pentyl sulfonate or sulfonic acid groups are combined with non-polar propyl groups. Neo-pentyl sulfonate PPDs give rise to defined supramolecular assembly structures, irrespective of their amphiphilic surface functionalization or size. In contrast, the self-assembly of PPDs with sulfonic acid substitution exhibits a pronounced dependence upon substitution pattern and generation. In particular, the Janus dendrimers demonstrate an increased tendency toward self-assembly compared to their patched counterparts. This trend is more pronounced for G2 than for G1 PPDs.
Gesehen am 01.08.2025